Compras governamentais e o gerenciamento de aquisições: aplicação de boas práticas do PMBOK no setor público - Costa, Renato Eliseu [UNIFESP] (2019)
Regardless of the precautions required by Federal Law 8.666/1993 on the length of constitutional principles and the advances that have been building in the field of public acquisitions in the last 15 years, there are still recurrent criticisms of inefficiency, inefficiency, lack of planning and control of public procurement. On the other hand, among the several ways that can improve Purchasing Acquisition Management, in recent years, the Project Management Body of Knowledge (PMBOK) Guide has been highlighted. Considering that the PMBOK presents the recognized "good practices" in procurement management, this work aimed at analyzing the possibilities of applying the processes and practices proposed in the Procurement Management, arranged in the PMBOK, in the area of Public Procurement, especially for the bidding procedures in the Competition modality, verifying if it is possible to make improvements of processes and economy for the public power, without disrespecting the constitutional principles. For both a descriptive and exploratory methodology was adopted, in a case study approach, adopting This is a form of qualitative research.It is possible to affirm that there is much room for process and economy improvements for the public power, without disrespecting constitutional principles, or even without disrespecting existing legislation - being able to update it to new technologies and practices by introducing of tools already consolidated in private initiative, such as project management through the PMBOK model.